CAPACite d’AssiMiLAtion du ChoLestéroL Chez les bactéries lactiques. - GUERNOUG, NADJET (My University, 2021)
This study aims to analyze the article "Ability of lactic acid bacteria isolated from mink to remove cholesterol: in vitro and in vivo studies by (Hanlu et al,2013)". The cholesterol-lowering property of lactic acid bacteria (LAB) isolated from mink is evaluated. Two strains, Enterococcus faecium MDF1104 and Lactobacillus plantarum MDL1118, were shown to remove cholesterol from broths of natural hen egg yolk and skimmed milk. The cholesterol in hen egg yolk was reduced by 58.15% and 38% by L. plantarum and E. faecium, respectively. When the bacteria were used in combination, 48.95% (p < 0.01) of cholesterol was removed from skimmed milk. Experimental mice remained healthy when fed different doses of the LAB, and the total serum cholesterol concentration was the lowest (0.90mmol/L) (p < 0.01) when a combination of L. plantarum and E. faecium was used. Based this results is suggested that L. plantarum MDL1118, E. faecium MDF1104, or a combination of the 2 strains could be considered as promising cholesterol-lowering probiotics.
Keywords: lactic acid bacteria, cholesterol, assimilation, hypercholesterolemia.